2021
DOI: 10.1111/irv.12868
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, beliefs and practice of Egyptian healthcare workers towards seasonal influenza vaccination

Abstract: Background: Seasonal influenza vaccination is highly recommended for healthcare workers (HCWs) every year to protect them and reduce the risk of disease transmission at workplaces. Relatively few studies addressed influenza vaccination in the Eastern Mediterranean Region. Objectives:The main objective of this study was to explore the attitudes, beliefs and practice of Egyptian HCWs towards seasonal influenza vaccine.Methods: This is a nationwide cross-sectional study. Data were collected through self-administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Overall, about 60% of HCP infrequently received influenza vaccines over an eight-year period; this population with low influenza vaccine uptake was primarily physicians and HCP who worked in an outpatient setting. Similar trends in low influenza vaccination coverage have been seen among HCP in KAP studies in Honduras [17] , Costa Rica [18] , Egypt [19] , and parts of the Middle East [20] . This low coverage was also seen in the general HCP population recruited into this study but excluded from analysis.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Overall, about 60% of HCP infrequently received influenza vaccines over an eight-year period; this population with low influenza vaccine uptake was primarily physicians and HCP who worked in an outpatient setting. Similar trends in low influenza vaccination coverage have been seen among HCP in KAP studies in Honduras [17] , Costa Rica [18] , Egypt [19] , and parts of the Middle East [20] . This low coverage was also seen in the general HCP population recruited into this study but excluded from analysis.…”
Section: Discussionsupporting
confidence: 67%
“…We found that 18% of HCP surveyed reported lacking some basic knowledge of influenza and its vaccine, 75% did not believe they were susceptible to influenza, 43% had concerns about vaccination, and 48% did not recall their supervisor recommending influenza vaccination to them. These gaps in influenza vaccine knowledge and trust among healthcare personnel have also been reported in Peru and other countries [19] , [24] , [25] , [26] , [27] . Healthcare facilities could improve influenza vaccine education by providing continuing medical education credits for courses focused on influenza prevention and treatment.…”
Section: Discussionmentioning
confidence: 56%
“…Globally, an extensive variability in influenza vaccine coverage was reported across different regions [73][74][75][76][77]. This could be related to different policies adopted regarding influenza vaccination, including those related to compulsory vaccination, in addition to challenges associated with the procurement, storage and distribution of vaccines, particularly in low-to middle-income countries [28,78].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of seasonal influenza vaccine uptake in the last season was 30.7%, while the percentage of the “ever vaccinated” was 46.8%. [ 14 ] This study was designed to determine the prevalence of influenza vaccine hesitancy and the reasons for the hesitancy of HCWs and mothers of preschool children attending Zagazig Maternal and Child Healthcare (MCH) Center in Sharqia Governorate.…”
Section: Introductionmentioning
confidence: 99%